Protozoários “vilões ou mocinhos”? : a sua importância ecológica nos ecossistemas : uma proposta inclusiva para aulas de Ciências - Santos, Josefa Silva dos (2020)
This research brings reflections on how the group of free-living protozoa in aquatic environments, even with technological advances and research, are still neglected in ecological terms, has been presented in textbooks and by most teachers as villainous organisms despite to have varied functions in aquatic ecosystems, as regulators of algae and bacteria populations acting directly in the food chain of these environments. With this premise, our research problem focused on verifying whether the methodological approaches used in Science / Biology classes help students to reflect on the ecological function of protozoa in ecosystems. This research aimed to evaluate the form of protozoan approaches in the classroom; to discuss how textbooks provide access to knowledge about protozoa (do they address only pathological and parasitic cycles?); test innovative and inclusive teaching methods for understanding the ecological role of protozoa. The methodological path included to test learning active methods, such as collaborative learning and an innovative approach - STEAM, in addition to the development of an educational product - Didactic Sequence (SD), which aims to contribute to the teaching and learning process of students from II Elementary School. In the year 2019, the product was tested and validated in two classrooms (Urutau and Canário) of the seventh year of a State School located at Comodoro municipality, State of Mato Grosso. To achieve the objectives, the methodological path consisted of three stages: First, a survey of the studants; in the second, the application of a questionnaire defined as a pre-test, followed by the application of the educational product; third and the last step was the application of a post-test. Analyzing the results, it was found that 41% of the students in the Urutau class said they knew what a protozoan was, and in the pre-test, this same percentage still agreed that all protozoa are causes of disease. After applying the SD, the questions were redone to the class and, according to the data produced, 77% now knew what a protozoan was, and only 22% still agreed that every protozoan causes disease. Of the Canary classroom, in the pre-test, 24% replied that they knew what a protozoan was, also maintaining the same percentage for students who agreed that all protozoa cause disease. After applying the SD, the number of students who knew how to answer what a protozoa is, have increased to 86% against the 13.5% of students who agreed that all protozoa cause disease. Another important aspect observed in the results was that in the two groups surveyed, few students were able to answer what scientific research is in the two phases of the research; in the pre-test of the Urutau class, only 35% knew how to define it, decreasing to 31% in the post-test. In the Canary class, in the first phase, 33.5% of the students answered that they knew the meaning. In the following phase, after the post-test, only 36.5% said they knew. Regarding the areas of STEAM, it was found that the activities of Science attracted the attention of the students of the Urutau class, attractive to 50% of the students, and in the Canary class to 59% of the respondents. The students' notes indicated the relevance of how science classes should be taught, such as with laboratory activities to visualize cells and microorganisms, field activities, collaborative activities, films, games and rewards and mentioned that they should be like those of the project research development.